The effect of plant hormone indoleacetic acid (IAA) on hematological and biochemical parameters in mice (Bangladesh Journal of Physiology and Pharmacology, 2009)
The subacute toxicity of plant hormone indoleacetic acid (IAA) was studied on Swiss albino mice. The studies include the gross general observation such as changes in body weight, hematological profiles [total count of red blood cells (RBC) and white blood cells (WBC), differential count of WBC, platelet count, hemoglobin (Hb)%], biochemical parameters of blood [serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), serum alkaline phospatase(SALP), creatinine] and histopathology of the liver, kidney, lung, spleen, heart and brain of both control and experimental day-1 for consecutive 14 days, showed no significant change of hematological and biochemical parameters. No abnormalities were also found in the histopathology of the liver, kidney, lung, spleen, heart and brain in the experimental group of animals following same dose when compared with control group. This preliminary toxicological study suggests that the plant hormone indoleacetic acid (IAA) may be used safely for agricultural purposes and as an external preservative DOI: 10.3329/bjpp.v22i1.3561 Bangladesh J Physiol Pharmacol 2006; 22(1/2) : 5-8